The Influence of Motivation on The Quality of Health Care Services At Hasta Husada Special Surgery Hospital: A Scoping Review - Edy Wahyudi; Ariyanto, Eko; Krisna, Andy E (Management Science Research Journal, 2024)
The impact of motivation on the caliber of health worker services at Hasta Husada Special Surgery Hospital has been examined in earlier literature studies. This scoping review's goal is to map out previous research that evaluates how work motivation affects the caliber of services provided by health workers. Finding research questions, finding pertinent studies, choosing studies, mapping data, and gathering, summarizing, and reporting findings are the five primary steps of a scoping review. According to the scoping review's findings, the majority of studies conducted over a ten-year period (2013–2023) recognized that job motivation affected the caliber of hospital services. However, according to Cicilia Lihawa et al. (2016), Titi Nur Wahidah (2017), and Andreano C. Porotu'o et al. (2014), work motivation had no bearing on the quality of services.